Polychemotherapy in the Treatment of Melanoma - But , Olexandra; Khaytovych, Mykola (The Ukrainian Scientific Medical Youth Journal, 2025)
melanoma is one of the most aggressive malignant neoplasms originating from melanocytes. In many countries, including the United States, the incidence of melanoma is steadily increasing. In 2024, more than 100,000 new cases of melanoma were registered in the U.S., with over 8,000 deaths reported. The disease most commonly affects exposed areas of the body but may also involve mucous membranes, the eyes, and subungual regions.This work presents a clinical case of a 57-year-old male patient diagnosed with melanoma of the left shoulder, classified as lentigo maligna (Hutchinson’s freckle), stage T1N1M0, clinical group 2. The patient had a significant familial history of melanoma, with both his father and grandfather having been diagnosed with the disease. During the initial examination, a 13×15 mm lesion was observed, characterized by ulceration, dark pigmented spots, and enlarged lymph nodes in the left axillary region. Surgical intervention included tumor excision along with partial resection of the subcutaneous fat and underlying muscles. Histopathological examination confirmed the diagnosis of melanoma with metastases in two regional lymph nodes.Following surgery, the patient received three cycles of polychemotherapy with pembrolizumab, administered intravenously at a dose of 200 mg every four weeks. Pembrolizumab is a PD-1 inhibitor that activates T-cells and enhances the immune response against tumor cells. The treatment demonstrated a favorable outcome — no signs of disease recurrence or progression were observed during a one-year follow-up period. Side effects included fatigue and headache, which were successfully managed through lifestyle modifications and the administration of paracetamol.The clinical pharmacist played an important role in monitoring adverse effects, providing medication-related counseling, preventing drug interactions, and improving patient adherence to therapy.